Annual Meeting of the Society for Ethnomusicology - McAllester, David (International Library of African Music, 1964)
We had three days of very interesting meetings and there were several papers that I note would be of interest to Africanists: “Some Speculations on a Drum Chime Tradition in Buganda”, by Klaus Wachsmann; “Musical Instruments of Madagascar”, by Norma McLeod; “Ubakala Dance: A Special Festival”, by Judith Lynne Hanna; “The Musical Instruments of Equatoria, Sudan”, by Roxanne McCollester. One afternoon was spent in an interesting symposium: Music, Dance and Anthropology: Ten Years of Co-operation, and we paid visits to two notable collections of musical instruments, The Stearns Collection at the University of Michigan and the Freeman Collection, a private one, in Detroit.
Keywords: African Music